Performance of "Digital India Programme" in the Rural Education Sector in India – A Post-COVID Analysis - Bhageria, Tushar (Digital Repository of Theses - SSBM Geneva, 2023)
The purpose of this research is to analyze the performance of the Digital India program in Rural India. The research also aims to understand how impactful the program was during COVID’19. The study aims to analyze the results by using both Qualitative and quantitative methods of research. This mixed-methods approach allows for a comprehensive understanding of the research problem by capturing both numerical data and qualitative insights. Qualitative methods of research include observations and Interviews while quantitative method includes surveys. Based on the findings from all the sources of information, results were triangulated, and analysis is formed. The long-term goal of the research was to help policymakers and the government to take appropriate steps and actions to make the Digital India program a success. Also, since the program aims at various sectors of development including infrastructure, lifestyle, health, and education etc., with this paper it provided the deep analysis of how impactful the program has been in the various parts of the country for the education sector, specifically, rural India. As a result of the analysis, it was noted that the Digital India Programme has made some efforts to improve digital infrastructure in rural areas. However, challenges such as limited connectivity, infrastructure gaps, inadequate electricity supply, and inadequate access to devices persist, hindering the seamless implementation of digital education initiatives in rural India. The program has planned to expand access to digital education resources, online learning platforms, and e-content in rural India. While these plans will provide new learning opportunities to rural students, there are disparities in access due to the digital divide, particularly concerning internet connectivity and the availability of devices. From the research, it was well understood that no online medium was used to promote Digital education in rural India. It is evident that no or limited learning happened during COVID’19. Though some of the alternative teaching methods were adopted by teachers and schools including rotational study plans and home assignments etc. there was no mention of the usage of digital tools to provide education. This was due to a lack of Digital infrastructure in villages and unawareness of the program among teachers and students. While there were measures taken to promote offline education, there is a need to understand the importance of the digital medium and resolve the challenges at the earliest to mitigate the shortcoming of offline education.